Finance and Development, March 1984. (Finance and Development; Finance and Development ;, 1984)
This paper examines the IMF's role in the changing world. Faced with mounting domestic and external financial imbalances, numerous African countries adopted adjustment programs supported by the use of IMF resources during 1980-81. Considerable emphasis has been given to economic growth in programs under consideration and most aimed for an increase in economic growth during the program year. Although programs generally emphasized an improvement in the external sector position, medium-term considerations did not always allow for an improvement in the current account position.